Nonlinear Responses and Optical Limiting Behavior of Ag Nanoparticle Suspension - N Mansour (Journal of Sciences, Islamic Republic of Iran)
In this study, the nonlinear optical properties and optical limiting performance of the silver nanoparticles (AgNPs) in distilled water are investigated. The nonlinear absorption coefficient of the colloid is measured by the Z-scan technique. The optical limiting behavior of the AgNP suspension is investigated under exposure to nanosecond laser pulses at 532 nm. The results show that nonlinear scattering can increase the performance of the optical limiting. A theoretical analysis is suggested investigating the observed nonlinear behavior of the AgNPs. It will be shown that nonlinear light scattering occurs at high beam intensity due to induced refractive mismatch between the silver nanoparticles and water. The experimental Z-scan data is fitted with the proposed theoretical model and this has allowed extracting the values of nonlinear absorption coefficient, linear and nonlinear scattering coefficients for the AgNP suspension.